Cover Image. (1st July 2019) - Zhao, Wei; Yang, Jiancheng; Ni, Bingbing; Bi, Dexi; Sun, Yingli; Xu, Mengdi; Zhu, Xiaoxia; Li, Cheng; Jin, Liang; Gao, Pan; Wang, Peijun; Hua, Yanqing; et al.
Abstract : The cover image is based on the Original Research Toward automatic prediction of EGFR mutation status in pulmonary adenocarcinoma with 3D deep learning by Wei Zhao et al., DOI:10.1002/cam4.2233 . Design Credit: Ming Li, Wei Zhao, Jiancheng Yang and Ye Ge.